PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN ASIMETRI INFORMASI: PERAN KEPEMILIKAN KELUARGA - Susi Retna Cahyaningtias; Zuhrotul Isnaini; Sapto Hendri BS (Jurnal Riset Akuntansi, 2019)
Asymmetric Information is caused by differences in information between shareholders and management. The more information that’s having by management, makes management free to manage the company in order to increase the compensation obtained. The way to reduce Asymmetric Information is transparency through disclosure, one of which is Corporate Social Responsibility (CSR). This study aims to examine the effect of corporate social responsibility (CSR) and Asymmetric Information with the role of family ownership as a moderating variable. The research sample is manufacturing companies that went public in Indonesia from 2014 - 2017 and who met the requirements to be sampled as many as 68 observations. Hypothesis testing uses MRA (Moderated Regression Analysis) using EVIEWS 11. The results shown that companies incur CSR costs in the previous period increase information asymmetry in the current period but the Asymmetric Information period is not related to CSR in the next period. Family ownership does not moderate the relationship between the previous period's CSR with the current period's Asymmetric Information and the current period's Asymmetric Information with the next period's CSR. The family ownership variable has two functions, namely as a predictive variable (independent) and a moderator homologiser, which means the family ownership variable has the potential to be a moderating variable.